SIKAP SOSIAL SISWA ANTARA MODEL PEMBELAJARAN KOOPERATIF PBL DAN PjBL - Helita Multisari; Yon Rizal; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2015)
This study aims to compare the social attitudes of student by using the model of PBL and PjBL Model against social attitudes of student in the subject of Economics. The method used in this study is the experimental method with a comparative approach. The population around the ten grade students and a sample of 128 students to 64 students. The result showed that: honest attitude of student in PBL models is higher than in the PBL model, attitudes responsinbility of student in the PjBL model is higher than in PBL models. The attitude of cooperation on the model of PBL students is higher than in the PjBL model. Mannered attitude of student in PBL models higher than in the PjBL model and confident attitude of students in PBL models is higher than in the PjBL model.Penelitian ini bertujuan untuk membandingkan sikap social siswa denagn menggunakan model PBL dan Model PjBL terhada sikap social siswa pada meta pelajaran Ekonomi kelas X. Metode yang digunakan dalam penelitian ini adalah metode penelitian eksperimen dengan pendekatan komparatif. Populasi dalam penelitian ini seluruh siswa kelas X yang berjumlah 128 siswa dan sampel berjumlah 64 siswa. Hasil penelitian menunjukan bahwa: Sikap jujur siswa pada model PBL lebih tinggi dibandingkan pada model PjBL, Sikap tanggung jawab siswa pada model PjBL lebih tinggi dibandingkan pada model PBL. Sikap kerjasama siswa pada model PBL lebih tinggi dibandingkan pada model PjBL. Sikap santun siswa pada model PBL lebih tinggi dibandingkan pada model PjBL dan sikap percaya diri siswa pada model PBL lebih tinggi dibandingkan pada model PjBL.Kata kunci: pbl, pjbl, sikap sosial